N′-[(5-Chloro-1H-indol-3-yl)methylene]-3,4,5-trihydroxybenzohydrazide - Khaledi, Hamid (International Union of Crystallography, 2008)
The two aromatic parts of the title compound, C(16)H(13)ClN(3)O(4), are connected through a conjugated –CH=N–NH–C(O)– fragment, giving an almost planar molecule (r.m.s. deviation 0.08 Å). In the crystal structure, adjacent molecules are linked by N—H⋯O and O—H⋯O hydrogen bonds into a three-dimensional network.